Predictors of myositis in mixed connective tissue disease: a multicentre retrospective study - Melo, A. T. (2024)
Objectives: We aimed to identify clinical and serological predictors of myositis in mixed connective tissue disease (MCTD). Methods: We performed a nationwide, retrospective, multicentre study including adult-onset MCTD patients fulfilling at least one of the following diagnostic criteria: Sharp’s, Kasukawa, Alarcón-Segovia, or Kahn’s. Univariable analysis was performed using Chi-square, Fisher exact, Student’s t or Mann-Whitney U tests, as appropriate. Multivariable analysis was performed using binary logistic regression. Results: Ninety-eight patients were included. Myositis was observed in 43.9% of patients, of whom 60.5% had myositis at disease onset. Proximal muscle weakness was described in 30 patients with muscle involvement (70%). Gastrointestinal involvement was identified in 28% and respiratory involvement in 29% of myositis patients. In the same subgroup of patients, 41.7% had a myopathic pattern on electromyography, and 47.1% had histological myositis features in the muscle biopsy. Fever (OR=6.96, p=0.022) was an independent predictor of myositis, regardless of sex, age at diagnosis, ancestry, and respiratory involvement. African ancestry (OR=8.39, p=0.019), leukopenia at the disease onset (OR 6.24, p=0.021), and younger age at diagnosis (OR=1.07/year, p=0.035) were identified as independent predictors of myositis at disease onset, regardless of sex and scleroderma pattern in capillaroscopy. Conclusions: Myositis is a common manifestation of MCTD, even at the disease onset. African ancestry, leukopenia at the disease onset, younger age at diagnosis, and fever should prompt a thorough evaluation for myositis.